Contribution of University Scientists into the Development of Ukrainian Geographic Science and Education - Inna Shorobura (Pedagogical Discourse, 2015)
Development of geographic science as a precondition of forming school geographic education in Ukraine has been analyzed in the article. Geography from the set of separated data turns into the system of scientific knowledge, which favours forming school geographic education in Ukraine. Activity of Kyiv, Lviv, and Kharkiv Universities has been studied. Contribution into the development of Ukrainian geographic science of S.Sharanevych (initiated teaching geographic disciplines), O.Kolberh (studied Pokuttia and Volyn), V.Shukhevych (ethnographic studies of Hutsulshchyna), S.Rudnytskyi (conducted researches on geography of Ukraine), I.Levakovskyi (initiated Kharkiv school of geomorphologists), A.Krasnov (founded natural-geographic school), P.Brounov (became one of the organizers of meteorological network in Prydnistrovya), K.Feofilaktov (formed geologic scientific school), A.Kolosovskyi (founded network of meteorological points in the South-West of Russia and Odesa magnate- meteorological observatory) and others has been offered. The role in the development of geographic science of such scientific societies as: Russian geographic society, Polish society of naturalists  named after M.Kopernik, Crimean society, Kyiv society of researchers of nature etc. has been cleared out.